The Effectiveness of Multimedia-Based Storytelling Methods in Improving Elementary School Students' Understanding of Islamic History - Siti Zulaekhah; Mustafa Ahmet; Hamidatun Nihayah (Research Journal on Teacher Professional Development, 2025)
The low understanding of students on religious history materials, especially the story of the migration of the Prophet Muhammad to Medina, encourages the need for innovation in learning strategies that are able to attract interest and increase student involvement. This study aims to analyze the improvement of the learning ability of grade IV students of SD Negeri 3 Kedungleper Bangsri, Jepara, through the application of multimedia-based storytelling learning methods to the material. The research uses a Classroom Action Research (PTK) approach with a two-cycle design, each including the stages of planning, implementation, observation, and reflection. The research subjects consist of 15 grade IV students in the 2024/2025 academic year. Data was collected through formative tests, observation of student activities, and documentation, then analyzed descriptively, qualitatively, and quantitatively to measure improvement in understanding and participation. The results showed a significant improvement: the average formative test score rose from 76 in cycle I to 90 in cycle II, while the average score of student activity observation increased from 17.6 to 27.5. These findings prove that multimedia-based storytelling methods are effective in strengthening concept understanding while increasing students' emotional and cognitive involvement with Islamic history materials. This research makes an original contribution to the development of a religious learning approach that is contextual, interesting, and in accordance with the characteristics of elementary school-age students, and can be adapted to other religious history materials.